PENGARUH KOMPETENSI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA SMPN 1 PANJI KABUPATEN SITUBONDO - Arinata, Selfi; Soeliha, Siti; Ciptasari, Ayu Dita Windra (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Human resources are valuable assets and function as the main driving force behind every action or activity of an organization. An organization really needs a professional and skilled workforce to contribute optimal performance in achieving the goals set by the organization's leadership. The aim of this research is to analyze and test the influence of competency and work environment on teacher performance through job satisfaction as an intervening variable at SMPN 1 Panji Situbondo. The population used in this research were 36 teachers at SMPN 1 Panji Situbondo. This sampling technique is saturated sampling. Data analysis and hypothesis testing in research uses Structural Equation Models - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Competence has a significant positive influence on job satisfaction, Motivation has a significantly positive influence on job satisfaction, Work environment has a significantly positive influence on job satisfaction, Competency has a positive but not significant influence on teacher performance, Motivation has a positive influence but not significant on teacher performance, work environment has a positive but not significant effect on teacher performance, job satisfaction has a significant positive effect on teacher performance. Then the results of the indirect influence hypothesis test show that Competence on teacher performance through job satisfaction has a significant positive effect, Motivation on teacher performance through job satisfaction has a significant positive effect, Work environment on teacher performance through job satisfaction has a significant positive effect